Beyond amino acid sequence: disulfide bonds and the origins of the extreme amyloidogenic properties of insulin's H‐fragment. (26th April 2019) - Dec, Robert; Koliński, Michał; Dzwolak, Wojciech
Abstract : The presence of disulfide bonds affects the protein stability and therefore tendency to misfold and form amyloid‐like fibrils. Insulin's three disulfide bridges stabilize the native state and prevent aggregation. Partial proteolysis of insulin releases highly amyloidogenic and inherently disordered two‐chain 'H‐fragment' retaining insulin's Cys7A‐Cys7B and Cys6A‐Cys11A disulfide bonds. The abrupt self‐association of H‐fragment monomers into fibrils is suppressed in the presence of disulfide‐reducing agent. These circumstances make the H‐fragment an interesting model to study the impact of disulfide bonds on amyloidogenesis beyond the 'stabilization‐of‐the‐native‐state' paradigm. Here, we investigate fibrillization of various synthetic peptides derived from the H‐fragment through modifications of Cys7A‐Cys7B/Cys6A‐Cys11A bonds. In comparison to H‐fragment, aggregation of a two‐chain 'AB' analog lacking Cys6A‐Cys11A bond is decelerated, while the alternative removal of Cys7A‐Cys7B bond releases a non‐aggregating B‐chain and a highly amyloidogenic 'ACC' fragment containing the intrachain Cys6A‐Cys11A bond. Our analysis, supported by calculations of configurational entropy, suggests that Cys6A‐Cys11A bond is a key factor behind the explosive self‐association of H‐fragment. The bond restricts the conformational space probed by nucleating monomers which is reflected by an approximately 2.4 kJ·mol −1 K −1 decrease in entropy. The fact that the intact Cys6A‐Cys11A bond promotes fibrillization of the H‐fragment is remarkable in light of the previously established role of the same disulfide bond in preventing formation of insulin fibrils. Our results imply that a single disulfide bond within a folded protein and its fragment may play entirely different roles in aggregation and that this role may evolve with progressing phases of misfolding. Abstract : The role of disulfide bonds in protein amyloidogenesis changes radically with the shifting conformational context. A single Cys6A‐Cys11A disulfide bond which prevents misfolding of insulin becomes a powerful pro‐fibrillization factor in the highly amyloidogenic H‐fragment of the protein. This phenomenon arises from restriction of the conformational space of nucleating H‐monomers by the topological loop closed by Cys6A‐Cys11A bond.